1999
DOI: 10.3758/bf03211536
|View full text |Cite
|
Sign up to set email alerts
|

Masked priming of words and nonwords in a naming task: Further evidence for a nonlexical basis for priming

Abstract: Masked priming effects in word identification tasks such as lexical decision and word naming have been attributed to a lexical mechanism whereby the masked prime opens a lexical entry corresponding to the target word. Two experiments are reported in which masked repetition priming effects of similar magnitude were obtained with word and nonword targets in a naming task. Masked orthographic priming was more stable for word than for nonword targets, although morphological primes produced no advantage beyond that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
42
1

Year Published

2000
2000
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(48 citation statements)
references
References 46 publications
5
42
1
Order By: Relevance
“…It should be noted, furthermore, that experiments involving the masked repetition priming procedure have generally resulted in facilitation effects for noncognates as well as cognates (e.g., de Groot & Nas, 1991;Gollan, Forster, & Frost, 1998), an outcome that challenges our claim that lexical representation depends on meaning and form. Although the claim that standard repetition priming is influenced by conscious episodic processes cannot be ignored, masked repetition priming is also open to extralexical interpretation, on the basis of evidence that, first, form priming may be observed for nonwords (Masson & Isaak, 1999) and, second, semantic priming may be observed in the absence of stimulus identification when degraded displays are used (Marcel, 1983). Our argument is, then, that performance on these tasks reflects different sets of processes.…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted, furthermore, that experiments involving the masked repetition priming procedure have generally resulted in facilitation effects for noncognates as well as cognates (e.g., de Groot & Nas, 1991;Gollan, Forster, & Frost, 1998), an outcome that challenges our claim that lexical representation depends on meaning and form. Although the claim that standard repetition priming is influenced by conscious episodic processes cannot be ignored, masked repetition priming is also open to extralexical interpretation, on the basis of evidence that, first, form priming may be observed for nonwords (Masson & Isaak, 1999) and, second, semantic priming may be observed in the absence of stimulus identification when degraded displays are used (Marcel, 1983). Our argument is, then, that performance on these tasks reflects different sets of processes.…”
Section: Discussionmentioning
confidence: 99%
“…We believe that effects in masked priming occur when primes and targets share overlapping representations (e.g., Frost et al, 1997, though see Masson & Isaak, 1999, for arguments favouring a nonlexical locus for masked priming effects). Thus, those prime-target pairs which share the same lexical stem, and therefore have overlapping lexical entries, such as the + M+ S+ O pairs in Experiments 1 and 2, should show signi cant facilitation in masked priming, while pairs which do not share a lexical stem will show priming effects (facilitatory or inhibitory) only at later stages of visual word recognition.…”
Section: The Classical Approachmentioning
confidence: 99%
“…Morphological effects in masked priming have been shown in the absence of semantic priming effects in Hebrew (Frost et al, 1997; SOA = 43 ms). They have also been demonstrated in the absence of orthographic priming effects in French (Grainger, Cole, & Segui, 1991; SOA = 64 ms) and in Dutch (Drews & Zwitserlood, 1995; SOA = 66 ms), though Masson and Isaak (1999) failed to nd such effects when they examined priming of irregular in ectional morphology (kept/keep) in English using the naming task. One aim of the research reported here, then, was to determine whether effects of derivational morphology are obtained in English masked priming in the absence of priming effects for semantically and orthographically related items.…”
mentioning
confidence: 99%
“…The visual representation of the prime in lower-case will then appear for 50 ms, and followed by the target in upper-case instantly. The target will remain on the screen until the participant responds or a 2500 ms timeout is reached (Forster, 1999(Forster, , 2003Masson & Isaak, 1999). For example, honeymoon is the masked prime, and the non-head constituent honey is the target.…”
Section: Libben Et Al (2003) Investigated the Processing Of English mentioning
confidence: 99%